Kinetic models of the extraction of vanillic acid from pumpkin seeds - Mitić Milan; Janković Sonja; Mašković Pavle; Arsić Biljana; Mitić Jelena; Ickovski Jovana (Open Chemistry, 2020)
Vanillic acid is used in the food industry and perfumery, and the optimization of its extraction process from the natural source is important for saving time and money. The presence of vanillic acid in pumpkin seeds was proven using HPLC analysis. Computational optimization of the extraction shows that for the concentration of ethanol 40% and solmodul: V/m=20, the optimum condition for the extraction of vanillic acid from pumpkin seeds was 100 min and 450C. The estimation of fitting for each kinetic model to the experimental kinetic data was performed using the root mean square, standard deviation, and the correlation coefficient. Ponomarev model was shown as the most suitable with the highest accuracy among the six considered kinetic models. The enthalpy and entropy changes were positive, while the Gibbs free energy was negative and decreased when temperature increased during the thermodynamic analysis. Therefore, the extraction of vanillic acid from pumpkin seeds was endothermic, spontaneous, and irreversible.